Iterative Channel Estimation with Data-Aided Interference Cancellation for Non-Orthogonal Multiple Access - Sosnin, Sergey D.; Xiong, Gang; Kwak, Yongjun (2018 IEEE 88th Vehicular Technology Conference (VTC-Fall), 2018)
In the 5 th generation of mobile cellular systems, non-orthogonal multiple access (NOMA) is being considered as a potential candidate for uplink (UL) multiple access (MA) in addition to the basic orthogonal multiple access scheme in order to support various usage scenarios including small packet transmissions, support of a massive number of users, and low latency and high reliability services. Since for NOMA, multiple users transmit uplink data packet in the same time and frequency resource, it is difficult to accurately estimate the channel coefficients from reference signals, especially if the reference signal itself suffers from interference from other users. This paper proposes a novel channel estimation algorithm which utilizes iterative interference cancellation operation in a data-aided manner in reference signal. This iterative channel estimation algorithm with data-aided interference cancellation provides improved channel estimation and overall link level performance at NOMA receiver.